Effects of an underwear-type hip abduction orthosis on sitting balance and sit-to-stand activities in children with spastic cerebral palsy - Kusumoto, Yasuaki (J Phys Ther Sci, 2018)
[Purpose] Hip dislocation and subluxation are common in patients with cerebral palsy (CP). Hip abduction orthoses are used to prevent and treat these problems. This study investigated the effects of an underwear-type hip abduction orthosis on sitting balance and sit-to-stand (STS) activity in children with spastic CP. [Participants and Methods] This trial had a cross-over design. Eight children aged 6 to 18 years old with spastic CP and Gross Motor Function Classiﬁcation level III and IV were randomly allocated to groups with or without use of the underwear-type hip orthosis. The trunk impairment scale (TIS) score was evaluated and the 5-times sit-to-stand test (FTSST) was conducted with and without the underwear. [Results] The dynamic sitting balance scores in the TIS and FTSST showed significant improvement with use of the orthotic underwear. [Conclusion] The dynamic sitting balance scores of the TIS and FTSST were higher, thus indicating better stability, when wearing the orthosis underwear. Thus, it was suggested that underwear-type hip abduction orthoses are effective for promoting sitting balance and STS activities in children with spastic CP.